P432 Barriers to prescribing anti-TNF therapy in inflammatory bowel disease (IBD) across newly industrialised emerging market countries: an analysis of the 'EXPLORE' study. (25th January 2019) - Ye, B D; Yamamoto Furusho, J K; Rana Qasim Khan, M; Fadeeva, O; Demuth, D; Qian, J; Khalif, I L; Chia-Hung, T; Toruner, M; Othman, A H; Chan, W; Ponce de Leon, E; et al.
Abstract: Background: Physician challenges to prescribing anti-tumour necrosis factor (TNF) therapy among patients with ulcerative colitis (UC) and Crohn's disease (CD) in real-world clinical practice remains limited in the newly industrialised countries in APAC, Latin America (LatAm), and Russia, Middle East (RME) regions. We aimed to assess physician-perceived barriers to prescribing anti-TNF therapy in local settings. Methods: The EXPLORE study is a chart review of IBD patients describing indicators and predictors of suboptimal response to anti-TNF therapy. It comprises a cross-sectional survey (completed during June 2017 till June 2018) of IBD specialists to identify local barriers to prescribing anti-TNF in real clinical practice, including those perceived to be faced by non- IBD GI specialists managing IBD patients. Results: The survey was completed by 73 IBD specialists. In 2016, the median (min–max) number of biologic-naïve UC and CD patients referred to IBD specialist sites was 30 (1–811) and 40 (2–1000), respectively. Amongst IBD patients eligible for anti-TNF therapy who did not receive it, estimates were higher for CD (median [min–max]: 30% [0–100%]) compared with UC (20% [0–100%]). Among IBD specialists, 'patient affordability' (51%), 'patient fear of side effects' (47%), and the 'complex reimbursement process' (33%) were the three most frequent barriers to prescribing anti-TNF therapy. For non-IBD GI specialists, 'physician lack of experience with anti-TNF therapy' (48%), 'patient affordability' (47%), and 'patient fear of side effects' (45%) and 'perceived safety risk' (45%) were the three most common perceived barriers. Regional differences are shown in Table 1. Hospitals were the most common setting to administer anti-TNF therapy for 78%, 67%, and 46% of patients in APAC, RME, and LatAm, respectively; however, 'lack of staff in infusion centres' (36%) and 'low numbers of infusion centres' (32%) were frequently reported challenges. Conclusions: EXPLORE is one of the first IBD studies of its kind conducted in the newly industrialised countries. The conducted physician's survey within this study identified key barriers to prescribing anti-TNF therapy. This analysis highlighted an unmet medical need, where a large proportion of IBD patients eligible for biologic therapy did not receive it. Better biologic reimbursement coverage, physician education strategies, along with availability of safer biologic therapies and greater infusion capacity, may be required in these countries to improve IBD patient management.